1974
DOI: 10.1017/s000335610002290x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary crude protein concentration and time of weaning on milk production and body-weight change in the ewe

Abstract: Twenty-seven North Country Cheviot ewes, each carrying twin foetuses and having a mean body weight at 6 weeks prior to parturition of 81 kg were individually penned and offered a constant daily intake of 16-75 MJ metabolizable energy during the last 6 weeks of gestation. At parturition the ewes were allocated to one of three dried grass/concentrate diets containing (1) 10-3, (2) 13-6 or (3) 16-9 % crude protein (CP) and 10 MJ metabolizable energy (ME) per kg. The mean daily CP intakes for diets 1 to 3 were 273… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
0

Year Published

1981
1981
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 12 publications
3
16
0
Order By: Relevance
“…The higher milk production obtained at high level of CP (P< 0.05) seems to be the direct consequence of a higher daily protein intake, since according to Robinson et al (1974), when the intake of digestible organic matter remains constant, milk production increases as the crude protein/metabolizable energy (CP/ME) ratio increases. This response is more intense when the ewes are submitted to energy restrictions or when the CP/ME ratio does not exceed 70 g/Mcal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher milk production obtained at high level of CP (P< 0.05) seems to be the direct consequence of a higher daily protein intake, since according to Robinson et al (1974), when the intake of digestible organic matter remains constant, milk production increases as the crude protein/metabolizable energy (CP/ME) ratio increases. This response is more intense when the ewes are submitted to energy restrictions or when the CP/ME ratio does not exceed 70 g/Mcal.…”
Section: Discussionmentioning
confidence: 99%
“…This response seems to be enhanced in ewes with high restrictions in energy intake (Robinson et al, 1974;, although positive responses have also been found with energy intake close to the theoretical requirements (Gonzalez et al, 1984). This phenomenon can be due either to a greater mobilization of body reserves (Robinson et al, 1974) or to an increase in the efficiency of utilization of these reserves for milk production (Cowan ef al, 1981 ).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas dairy cattle may have considerable reserves of body fat which can be mobilized in early lactation to meet deficits in energy supply (Flatt et al 1967), it is generally considered that, relatively, very limited amounts of body protein can be drawn upon when dietary protein supply is inadequate. Both for ewes (Robinson et al 1974) and for cows it has been shown that a higher dietary protein concentration is required when animals are in negative energy balance and that additional protein appears to facilitate greater mobilization of body fat. In the experiment reported by Orskov et al (1977), Friesian cows in early lactation were given amounts of food sufficient to provide for a daily yield of only 10 kg fatcorrected milk (FCM), and were given post-ruminal infusions of casein or glucose.…”
mentioning
confidence: 99%
“…Indeed, milk production in ewes varies with the percentage of CP in the diet (Robinson et al 1974(Robinson et al , 1979Gonzalez et al 1982). Ewes receiving 340 g d -1 or 415 g d -1 of protein produced 21 and 28% more milk, respectively, than ewes receiving 273 g d -1 (Robinson et al 1974).…”
mentioning
confidence: 99%
“…Indeed, milk production in ewes varies with the percentage of CP in the diet (Robinson et al 1974(Robinson et al , 1979Gonzalez et al 1982). Ewes receiving 340 g d -1 or 415 g d -1 of protein produced 21 and 28% more milk, respectively, than ewes receiving 273 g d -1 (Robinson et al 1974). Determination of the amount of CP needed in the diet of lactating ewes depends not only on the extent to which the supplementary protein escapes the rumen undegraded, but also on the magnitude of energetic deficiency for maintenance and milk production (Robinson et al 1974).…”
mentioning
confidence: 99%